Top-Gate Short Channel Amorphous Indium-Gallium-Zinc-Oxide Thin Film Transistors with Sub-1.2 nm Equivalent Oxide Thickness - Han, Kaizhen (Institute of Electrical and Electronics Engineers Inc., 2022)
10.1109/jeds.2021.3116763